Care choices in Europe: To Each According to His or Her Needs? - Dörte Heger; Thorben Korfhage (SAGE Publishing, 2018)
Growing long-term care (LTC) needs represent a major challenge for our aging societies. Understanding how utilization patterns of different types of care are influenced by LTC policies or changes in the population composition such as age patterns or health can provide helpful insight on how to adequately prepare for this situation. To this aim, this paper explores how individuals choose between different forms of LTC. We exploit variation between countries as well as between individuals within countries using data from the Survey of Health, Ageing, and Retirement in Europe (SHARE). Using nonlinear decomposition techniques, we break down the difference in utilization rates between countries into differences based on observed sociodemographic and need-related characteristics and differences in the impacts of these characteristics, which allows us to identify the drivers behind differences in the formal-informal care mix. Our results show that a substantial fraction of the observed country differences can be explained by differences in impacts. We argue that this is a result of the different incentives provided by the different LTC systems.